The Effect of Good Corporate Governance on Financial Performance and Its Impact on Competitive Advantage (Empirical Study on Property and Real Estate Sub-Sector Companies Listed on the Idx for the Periode 2017 – 2020) - Nurul HIDAYAH; Aldilla PUTRIATAMA (Indonesia Strategic Sustainability, 2023)
This study aims to determine the relationship between Good Corporate Governance on competitive advantage mediated by financial performance. Good Corporate Governance is proxied by independent commissioners, audit committees and institutional ownership. Financial performance is measured by Return on Assets (ROA). The population in this study is the property and real estate sub-sector companies listed on the Indonesia Stock Exchange from 2017-2020. The data collection method used is purposive sampling. The number of final samples that are eligible to be used as research samples is 68 samples. The analysis technique used is path analysis. The results of this study indicate that independent commissioners do not affect ROA, while audit committees and institutional ownership affect ROA. Independent commissioners and audit committees affect competitive advantage, while institutional ownership does not. After conducting path analysis, ROA cannot mediate the effect of independent commissioners and audit committees on competitive advantage. In contrast, ROA can mediate the impact of institutional ownership on competitive advantage.